Tinjauan Hukum Islam Terhadap Fenomena Memberikan Dan Mendapatkan Gift Pada Live Streaming Aplikasi Youtube - Wijaya, Adi Candra; Khairunnisa, Khairunnisa; Nasution, Anggi Harnum Lestari; Fatmasari, Lilis; Az-zahra, Resa Salma Salsabila; Fajrussalam, Hisny (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
The development of digital technology has brought about significant changes in human interactions and transactions, especially through live streaming platforms such as YouTube. The phenomenon of viewers giving digital gifts to content creators during live broadcasts creates a new economic ecosystem that allows creators to earn directly from fan support. However, in the context of a Muslim society, this practice raises questions regarding its compatibility with the principles of Islamic law. This article aims to examine the phenomenon of gifting from a Shariah perspective, taking into account the transaction mechanism, socio-economic impact, as well as the views of contemporary scholars. This research uses a qualitative method with a literature study approach and fatwa analysis, referring to the fatwas of scholars related to digital transactions. The results show that gifting can be categorized as a halal grant, as long as it is done with good intentions, Shariah-compliant content, and transparent and fair transaction mechanisms. The findings provide guidance for the Muslim community in participating in the digital economy without violating religious principles, and encourage further discussion on the application of Islamic law in the context of the evolving digital economy. Keywords:  Islamic Law, Live Streaming, Youtube, Gift